A Risk-Based Debt Sustainability Framework : Incorporating Balance Sheets and Uncertainty - Gray, Dale (IMF Working Papers; Working Paper, 2008)
This paper proposes a new framework for the analysis of public sector debt sustainability. The framework uses concepts and methods from modern practice of contingent claims to develop a quantitative risk-based model of sovereign credit risk. The motivation in developing this framework is to provide a clear and workable complement to traditional debt sustainability analysis which-although it has many useful applications-suffers from the inability to measure risk exposures, default probabilities and credit spreads. Importantly, this new framework can be adapted for policy analysis, including debt and reserve management.